Referentes sobre inclusión educativa para personas con discapacidad : líneas para pensar su potencial en el ámbito escolar. (2018)
The inclusion is proposed as a process of broad discussions at national as well as the international level that gradually gaining spaces to guarantee the education rights for all the people. First, it explores the normative that allows to understand the educative attention focused on people with disability. In order to identify the progress in the educative attention modalities, we search about the rights for the people with disability in countries like Argentina, Brazil, Chile, Colombia, and Ecuador, which have signed the Convention of the Rights of Persons with Disabilities. At the same time, we analyze other researches about experiences in educative inclusion in Colombia and in other Iberic-American countries to visualize tendencies and establish references to understand this fact and be able to understand the potential in the school environments allowing the emergence of a new field of knowledge in relation with the same process.